RADIOLARIAN EVIDENCE FOR EARLY CRETACEOUS (LATE BARREMIAN - EARLY APTIAN) SUBMARINE VOLCANIC ACTIVITY IN THE TETHYAN OCEANIC REALM PRESERVED IN KARABAGH (LESSER CAUCASUS) - Asatryan, Gayané; Danelian, Taniel; Sosson, Marc; Sahakyan, Lilit; Galoyan, Ghazar (Ofioliti, 2012)
Dating radiolarites in the ophiolitic sequences of Alpine mountain belts is important for the geodynamic reconstruction of Neo-Tethys in the Lesser Caucasus.However, radiolarian data from Karabagh are very rare. A moderately well-preserved radiolarian assemblage was obtained from radiolarites that overliepillow lavas cropping out west of the village of Vank in the mountainous region of Karabagh. The presence of the easily recognisable subspecies Aurisaturnaliscarinatus perforatus is of particular significance because it is the end member of a well studied lineage that went extinct in the early Aptian. Indeed, themiddle late Barremian - early early Aptian age range of this subspecies allows to suggest that submarine volcanic activity took place during this interval in theTethyan oceanic realm preserved in Karabagh. Given that this submarine volcanic event is more or less contemporaneous to the Aptian alkaline OIB-typelavas from the Vedi ophiolite, it is likely that the Karabagh lavas are also the expression of a volcanic activity associated to the emplacement of the sameoceanic volcanic plateau.